2004
DOI: 10.1007/s00421-004-1195-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lumbar extensor fatigue and fatigue rate on postural sway

Abstract: Falls from heights resulting from a loss of balance are a major concern in the occupational setting. Previous studies have documented a deleterious effect of lower extremity fatigue on balance. The purpose of this study was to investigate the effect of lumbar extensor fatigue on balance during quiet standing. Additionally, the effects of fatigue rate on balance and balance recovery rate were assessed. Eight center-of-pressure-based measures of postural sway were collected from 13 participants, both before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 41 publications
6
98
1
Order By: Relevance
“…In comparison with the control condition, significantly larger posterior sways have been shown during TS muscle vibration while standing on an unstable support surface. An increased sway due to lumbar muscle fatigue has already been shown by some studies [20,21]. This can be explained by the negative influence of fatigue on the muscle receptors and thereby on proprioception [2,14].…”
Section: Back Muscle Fatigue Conditionmentioning
confidence: 79%
See 1 more Smart Citation
“…In comparison with the control condition, significantly larger posterior sways have been shown during TS muscle vibration while standing on an unstable support surface. An increased sway due to lumbar muscle fatigue has already been shown by some studies [20,21]. This can be explained by the negative influence of fatigue on the muscle receptors and thereby on proprioception [2,14].…”
Section: Back Muscle Fatigue Conditionmentioning
confidence: 79%
“…Furthermore, Taimela et al concluded that lumbar muscle fatigue impaired lumbar position sense in patients with LBP and healthy subjects [19]. Some studies showed that lumbar extensors fatigue resulted in an increased postural sway in healthy individuals [20,21]. However, to the authors' knowledge, no studies have examined the possible relationship between back muscle fatigue and the selection of a proprioceptive postural control strategy in healthy individuals and in people with recurrent LBP.…”
Section: Introductionmentioning
confidence: 99%
“…The task of maintaining upright balance is a critical component in performing most daily activities. Numerous studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have investigated the effects of muscular fatigue on the regulation of bipedal quiet upright standing. Generally, a deterioration of postural control with muscular fatigue was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Zazulak et al (21) reported that trunk displacement was greater in athletes with knee and ACL injuries compared with uninjured athletes. It has been reported that core muscle fatigue decreased dynamic stability of the trunk and loss of balance control (3,6,18). Dynamic balance is define as the ability of an individual to maintain stability of the center of mass during movement and an essential component of many sports activities.…”
Section: Introductionmentioning
confidence: 99%